An Assistant Android Application "Help Me" Application - Elshamam, Nuri; Eshtawie, Mohamed; Elshamam, Malak (Conference On Engineering Science and Technology, 2021)
Many people find themselves in a situation where they feel threatened or scared for their lives. Those people sometimes might need assistance in carrying out certain projects or tasks or may require certain documents or would like to share certain helpful documents with other users. In this application we try to integrate all of these aiding functions and mobile technologies into one assistant application to help users who require such services, to obtain it easily in one place without any constraints. This application offers seven main functions: signing in/up, adding contacts, sending location using the panic button, asking for a request, doing a favour for a friend, uploading and downloading documents from the server, and how to use menu. We have used Java and XML for the development on the client-side and the Firebase services to develop and store data on the server-side alongside Node.js for server-side function development.
Keywords: Android applications; Coud security; Data offloading; Mobile technology; Panic Button